Comorbidities and Outcome of Geriatric COVID-19 Patients Admitted to Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: The 2019 Corona Virus illness (COVID-19)is a novel disease with a notable mortality risk, and it has been noted that older adults have a higher death risk from COVID-19.There was a scarcity of studies on comorbidity patterns and outcomes of COVID-19 in Bangladeshi geriatric patients. The study aimed to investigate comorbidity and outcomes of geriatric COVID-patients admitted to a tertiary hospital in Bangladesh.Materials and methods: This prospective observational study was carried out at Chittagong Medical College Hospital (CMCH) in Six months’ time duration from 01/07/2021 to 31/12/2021. 110 RT-PCR COVID-19-positive geriatric patients admitted to CMCH during the study period were included in the study. Consecutive sampling was followed in the study. The data collected included the patient's age, sex, comorbidities, severity of illness, and outcome.Results: The mean age was 60.0±7.4 years with a maleto-female ratio of 1.6:1. The most frequent comorbidity was hypertension (75.5%), followed by DM (68.2%), IHD(26.4%), COPD (18.2%), CKD (18.2%) and stroke(6.4%). Out of 110 patients, only 5 (4.5%) patients were free from any comorbidity, 31 (28.18%) patients hads ingle comorbidity, 40 (36.4%) patients reported having two comorbidities, and another 34 (30.9%) had  3 comorbidities. Thirty-seven (33.6%) patients expired, and seventy-three (66.4%) patients were recovered and discharged. Higher age, unvaccinated status, and higher number of comorbidities were significantly associated with mortality.Conclusion: The current investigation verified that in older COVID-19 patients, more comorbidities and age were linked to a higher risk of death.JCMCTA 2024 ; 35 (1) : 16-21